Digital approach for measuring dentin translucency in forensic age estimation - Simranjit Singh; Ramesh Venkatapathy; P Balamurali; NSC Charles; R Suganya (Journal of Forensic Dental Sciences, 2013)
Background: Dentin translucency is best suited for age estimation not only in terms of accuracy but also in terms of simplicity. Conventionally, translucency has been measured using calipers. Computer-based methods have been proposed for the same, although these required the use of custom-built software programs. Objectives: The objectives of the study were to use a simple digital method to measure dentinal translucency on sectioned teeth and to compare digital measurements to conventionally obtained translucency measurements. Materials and Methods: Fifty extracted permanent teeth were collected and were sectioned to 250 μm. Translucency measurements were obtained using the digital method and compared with those obtained using a caliper. Results: Correlation coefficients of translucency measurements to age were statistically significant for both methods (P < 0.001), and marginally higher for the conventional approach (r = 0.4671). Application of derived linear regression equations on an independent sample (n = 10) revealed a similar ability of both the methods to assess age to within ±5 years of the actual age. Conclusion: The translucency measurements obtained by the two methods were very similar, with no clear superiority of one method over the other. Hence, further studies on a large scale are warranted to determine which method is more reliable to estimate the age.